Creative tourism research: from a critical review of the literature to future research opportunities - Moleiro, Diogo (2023)
This paper presents a comprehensive analysis of the existing literature on creative tourism. Through a bibliometric review, existing research on this topic was analyzed using search keywords in the Scopus and ISI Web of Science databases. After the final selection, the articles were analyzed in terms of keyword co-occurrence using Vosviewer software as an analysis tool. Subsequently, a critical analysis of creative tourism was conducted, and finally, possible future research opportunities were proposed. The results show that research on creative tourism gravitates around four interrelated approaches, initially focusing on creative experiences and learning activities, then more consumption-related perspectives, then cooperation between creative entrepreneurs and the local community itself, which in turn leads to the development of new forms of cooperation between creative entrepreneurs, the local community, and new intermediaries. Finally, creative tourism adopts a new approach that fits relational tourism and is based on the co-creation of experiences that stimulates placemaking.